Sports governing bodies vs. antitrust 0 - 4? Sport and competition economics comments on the recent judgements of the European Court of Justice - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2025)
Commercial sports belong to the biggest entertainment industries in the world and, at the same time, are regularly raising antitrust concerns. This is partly due to the omnipresence of powerful market-internal regulators. These sport governing bodies set, implement, and enforce the rules and additionally engage in commercial activities. In a series of four judgments within less than a year, the European Court of Justice found (potential) antitrust violations in cases of deterring market entry, distorting competition, and exploiting players. This contribution adds economic comments to the predominantly legal literature on these judgements. It concludes that despite important steps in the right direction, more antitrust enforcement is necessary to protect competition in this unique entertainment industry vis-à-vis the presence of market-internal, private regulators. Next to limiting their scope (where the court provided progress), also the incentives for anticompetitive conduct must be addressed.
Keywords: K21; L40; L50; L83; Z20; 330; sport markets; sport governance; competition policy; antitrust; sports associations; institutions; market-internal regulators; European Court of Justice; competition economics; sports economics